2011
DOI: 10.1108/13598541111139044
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain integration and efficiency performance: a study on the interactions between customer and supplier integration

Abstract: Purpose – This research intends to investigate whether there are synergies that a firm could or should exploit by simultaneously implementing customer and supplier integration. In particular, the aim is to analyze the impact of customer integration on efficiency, and the moderating role of supplier integration. Design/methodology/approach – This study analyzes data from a sample of 200 manufacturing plants. Two hypotheses are tested through a hierarchical regression analysis. Customer and supplier integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
138
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(153 citation statements)
references
References 55 publications
(105 reference statements)
11
138
1
3
Order By: Relevance
“…Over the years, extant literature has been unspecific in defining SC performance, and particularly, its dimensions. Some previous research have focused on delivery and flexibility (Huo, 2012;Prajogo & Olhager, 2012), customer service (Vickery et al, 2003), efficiency (Danese & Romano, 2011;Prajogo & Olhager, 2012), and service performance (i.e. delivery and support) (Droge et al, 2012), among others.…”
Section: Sc Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, extant literature has been unspecific in defining SC performance, and particularly, its dimensions. Some previous research have focused on delivery and flexibility (Huo, 2012;Prajogo & Olhager, 2012), customer service (Vickery et al, 2003), efficiency (Danese & Romano, 2011;Prajogo & Olhager, 2012), and service performance (i.e. delivery and support) (Droge et al, 2012), among others.…”
Section: Sc Performancementioning
confidence: 99%
“…When SC is appropriately managed, the outcome is one of enhanced performance (Chopra et al, 2007). As business competition shifts from between individual entities to SCs, adoption of SC practices could offer competitive advantage in the face of fierce competition on the global market (Christopher et al, 2006;Danese & Romano, 2011). The integration of activities and processes among the members of the SC is usually referred to as SCM (Handfield & Nichols, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There are gaps in the results of studies in external integration involving supplier, where it is found that it does not have significant impact on company performance [3]. While the external integration involving customers does not significant impact on the performance of delivery [1].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is caused by a lack of clarity and consistency in what is to be measured in the implementation of integrative SCM [1]. The theoretical basis for justifying the role of integrative SCM implementation in improving competitiveness and performance of the company is still weak and this has been the cause of many debates [2,3]. It is important to carry out further study in relation to this finding, especially by using a contingency approach where the impact of integration of supply chain on competitiveness and performance is variable from upstream to downstream [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation